Implementation of ISAK 35: How Hospitals in West Sumatera Present Their Financial Statements? - Edmawati, Sri Dewi; Komalasari, Sanda Patrisia (Politeknik Ganesha Medan, 2024)
Hospitals are a form of non-profit entity. For accountability, hospitals should provide financial reports that comply with applicable accounting standards, namely ISAK No. 35. The purpose of this study is to see whether hospitals have implemented interpretation of financial accounting standard, namely Interpretasi Standar Akuntansi Keuangan (ISAK) No. 35. The limited amount of research on this subject makes us compelled to do so. This research is important to do in order to improve the quality of financial reporting in hospitals. ISAK No. 35 regulates the presentation of financial statements of non-profit oriented entities. The method used to achieve this purpuse is to carry out an analysis of financial reports and distribute questionnaires regarding the content of financial reports for hospitals that not provide access to their financial reports. The samples in this study were 22 major hospitals in Padang City and several hospitals outside Padang City in West Sumatra. The findings of this study are that only 2 from 22 hospitals have implemented ISAK 35. All BLU/BLUD government hospitals in this study implemented SAP, but not ISAK 35. This research provides information that financial reporting in hospitals is still inadequate, regardless of whether hospitals implement ISAK 35 or not. This research will provide data for the government to make various efforts to improve the quality of hospital financial reporting.